The Effects of Brain Serotonin Deficiency on Responses to High Fat Diet in Female Mice - Huq, Shama N.; Warner, Allison K.; Buckhaults, Kerry; Sachs, Benjamin D. (Frontiers in Neuroscience, 2021)
Clinical studies have reported an increased risk of depression and anxiety disorders among individuals who are obese, and women are more likely than men to suffer from depression, anxiety, and obesity. However, the effects of obesity-promoting diets on depression- and anxiety-like behavior remain controversial. A recent study from our group used the tryptophan hydroxylase 2 (R439H) knock-in mouse line to evaluate the impact of genetic brain serotonin (5-HT) deficiency on behavioral responses to HFD in male mice. That study indicated that chronic exposure to HFD induced pro-anxiety-like effects in the open field test and antidepressant-like effects in the forced swim test in wild-type (WT) males. Interestingly, the antidepressant-like effect of HFD, but not the anxiogenic effect, was blocked by brain 5-HT deficiency in males. The current work sought to repeat these studies in females. Our new data suggest that females are less susceptible than males to HFD-induced weight gain and HFD-induced alterations in behavior. In addition, the effects of chronic HFD on the expression of inflammation-related genes in the hippocampus were markedly different in females than we had previously reported in males, and HFD was shown to impact the expression of several inflammation-related genes in a genotype-dependent manner. Together, our findings highlight the importance of brain 5-HT and sex in regulating behavioral and molecular responses to HFD. Our results may have important implications for our understanding of the clinically observed sex differences in the consequences of obesity.